Integrasi Pemikiran Sistem untuk Digital Government: Systematic Literature dan Model Konseptual Holistik - Fuji Syaulend Utami; Galuh Fitria Nopita Anggi; Nasywa Dwi Aura; Vhaiz Alfarisy de Rekha; Jumiati Jumiati; Boni Saputra (CV. ITTC INDONESIA, 2025)
Digital transformation in public administration faces systemic complexities that require a holistic and integrated approach. Previous research shows that 68% of e-government projects fail due to fragmentary approaches that ignore systemic aspects. This study aims to integrate systems thinking principles in developing a conceptual framework for a holistic, adaptive, and sustainable digital public administration system. The study used a systematic literature review method of 20 journal articles and 2 academic books for the period 2015-2024. The research used content analysis to explore key patterns in the literature and develop an in-depth conceptual synthesis. The results identified five critical dimensions of an integrated digital administrative system: system architecture, digital capacity, integration mechanism, adaptive governance, and value creation process. The implementation of a systemic approach was shown to reduce implementation fragmentation by 45%, increase system utilization by 78%, and improve overall government effectiveness by 52%. This framework makes a theoretical contribution in filling the gap of systems thinking literature for digital government and provides practical guidance for sustainable digital transformation in public administration.